"Everything Has Beauty but Not Everyone Sees It": An Islamic Alternative to Assessing Beauty. Issue 3 (3rd May 2020) - Fahm, Abdulgafar Olawale
ABSTRACT: The constant reference to beauty ideals in all facets of contemporary culture, including work, sex, and religion as well as the constant exposure to images of "beautiful" women, which are ubiquitous in the mass media as the ideal, make a search for a categorical view a necessity. Through qualitative research approach, in which critical, content, and discourse analysis were applied on classical, as well as relevant contemporary materials on beauty, this study contributes an Islamic perspective to the discourse, and hinges its discussions on the primary sources in Islam (Qur'an and Hadith). The paper examines what the Qur'an and Hadith view as beauty and physical attractiveness. It was discovered that in Islam, beauty has five primary emphases: virtue, divine, nature, order, and proportion.